PREPARATION AND CHARACTERIZATION OF IRON SULPHIDE THIN FILMS BY CHEMICAL BATH DEPOSITION METHOD - Anuar Kassim; Tan WeeTee; Dzulkefly Kuang Abdullah; Atan Mohd. Sharif; Ho SoonMin; Gwee Siew Yong; Saravanan Nagalingam (Universitas Gadjah Mada, 2010)
FeS2 thin films have been deposited by using low cost chemical bath deposition technique. The films obtained under deposition parameters such as bath temperature (90 °C), deposition period (90 min), electrolyte concentration (0.15 M) and pH of the reactive mixture (pH 2.5). The thin films were characterized using X-ray diffraction and atomic force microscopy in order to study the structural and morphological properties. The band gap energy, transition type and absorption properties were determined using UV-Vis Spectrophotometer. X-ray diffraction displayed a pattern consistent with the formation of an orthorhombic structure, with a strong (110) preferred orientation. Atomic force microscopy image showed the substrate surface is well covered with irregular grains. A direct band gap of 1.85 eV was obtained according to optical absorption studies.